Nonisothermal analysis of extrusion film casting process using molecular constitutive equations - Pol, Harshawardhan; Banik, Sourya; Azad, Lal Busher; Thete, Sumeet Suresh; Doshi, Pankaj; Lele, Ashish K. (Rheologica Acta, 2014)
Extrusion film casting (EFC) is a commercially important process that is used to produce several thousand tons of polymer films and coatings. In a recent work, we demonstrated the influence of polymer chain architecture on the extent of necking in an isothermal film casting operation (Pol et al., J Rheol 57:559-583, 2013). In the present research, we have explored experimentally and theoretically the effects of long-chain branching on the extent of necking during nonisothermal film casting conditions. Polyethylenes of linear and long-chain branched architectures were used for experimental studies. The EFC process was analyzed using the 1-D flow model of Silagy et al. (Polym Eng Sci 36:2614-2625, 1996) in which the energy equation was introduced to model nonisothermal effects, and two multimode constitutive equations, namely the ``extended pom-pom'' (XPP, for long-chain branched polymer melts) equation and the ``Rolie-Poly stretch version'' (RP-S, for linear polymer melts) equation, were incorporated to account for the effects of polymer chain architecture. We show that the model does a better job of capturing the qualitative features of the experimental data, thereby elucidating the role of chain architecture and nonisothermal conditions on the extent of necking.
Keywords: Branched; Extrusion; Film; Linear; Necking; Nonisothermal; Polyethylene

Extrusion film casting of long chain branched polypropylene - Chikhalikar, Kalyani; Banik, Sourya; Azad, Lal Busher; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Kulkarni, Surendra; Gupta, Surendra; Doshi, Pankaj; Pol, Harshawardhan; Lele, Ashish K. (Polymer Engineering and Science, 2015)
Extrusion film casting (EFC) is an important melt processing operation which is extensively used to make polypropylene (PP) films. Linear PP shows significant amount of necking and draw resonance during EFC. One of the ways to reduce necking is to introduce long chain branches (LCB) on the polymer backbone. The long branches impart extensional strain hardening behavior thereby stabilizing the melt flow. In this work, we investigate the influence of long chain branching in polypropylene on the extent of necking in the EFC process. Laboratory scale EFC experiments were performed on homopolymer PP of linear and long chain branched architectures. Simulations of the EFC process were carried out using the one-dimensional flow model of Silagy et al., Polym. Eng. Sci.,36, 2614 (1996) into which we incorporate two different multi-mode molecular constitutive equations namely, the eXtended Pom-Pom' equation (XPP, for long chain branched PP) and the Rolie-Poly' equation (RP-S, for linear PP). Our experimental data confirm that presence of long chain branching in PP reduces the extent of necking and our numerical predictions show qualitative agreement with experimental data, thereby elucidating the role of chain architecture on the extent of necking. POLYM. ENG. SCI., 55:1977-1987, 2015. (c) 2014 Society of Plastics Engineers

Influence of macromolecular architecture on necking in polymer extrusion film casting process - Pol, Harshawardhan V.; Banik, Sourya; Azad, Lal Busher; Thete, Sumeet; Doshi, Pankaj; Lele, Ashish (30th International Conference of the Polymer-Processing-Society (PPS), 2015)
Extrusion film casting (EFC) is an important polymer processing technique that is used to produce several thousand tons of polymer films/coatings on an industrial scale. In this research, we are interested in understanding quantitatively how macromolecular chain architecture (for example long chain branching (LCB) or molecular weight distribution (MWD or PDI)) influences the necking and thickness distribution of extrusion cast films. We have used different polymer resins of linear and branched molecular architecture to produce extrusion cast films under controlled experimental conditions. The necking profiles of the films were imaged and the velocity profiles during EFC were monitored using particle tracking velocimetry (PTV) technique. Additionally, the temperature profiles were captured using an IR thermography and thickness profiles were calculated. The experimental results are compared with predictions of one-dimensional flow model of Silagy et al(1) wherein the polymer resin rheology is modeled using molecular constitutive equations such as the Rolie-Poly (RP) and extended Pom Pom (XPP). We demonstrate that the 1-D flow model containing the molecular constitutive equations provides new insights into the role of macromolecular chain architecture on film necking. D-1. Silagy, Y. Demay, and J-F. Agassant, Polym. Eng. Sci., 36, 2614 (1996).

Effect of plug temperature on the strain and thickness distribution ofcomponents made by plug assist thermoforming - Marathe, D.; Rokade, D.; Azad, Lal Busher; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Gupta, S.; Kulkarni, S.; Juvekar, Vinay A.; Lele, Ashish K. (International Polymer Processing, 2016)
Plug temperature is a key parameter affecting the thickness distribution of thermoplastic components made by plug assist thermoforming. For a specified pair of plug and plastic sheet, the variation in plug temperature can alter the coefficient of friction (COF) between the pair. We show here how the temperature dependence of COF influences the nature and extent of biaxial stretching of the sheet and consequently the thickness distribution of the thermoformed component. In the present study, high impact polystyrene (HIPS) sheets were thermoformed into axisymmetric cups using a plug-assist process in which the aluminum plug temperature (T-plug) was varied from ambient to above the glass transition temperature of HIPS (similar to 100 degrees C). Biaxial strain maps on the surfaces of the formed cups were measured and quantified using Grid Strain Analysis (GSA). Thickness distributions of the cups were also measured. Temperature dependent COF between HIPS and aluminum was determined independently using a rotational rheometer. The measured COF was low for T < 100 degrees C, whereas it increased appreciably at and above 100 degrees C. We conclude that when T-plug < 100 degrees C the HIPS sheet slips on the plug during forming, and this results in biaxial stretching of the base and walls of the formed cup. In contrast for T-plug > 100 degrees C, a significant reduction in the magnitude of slip is expected. Here the sheet is gripped at the clamp and by the plug during forming which causes reduced biaxial stretching of the base and increased uniaxial stretching of the walls of the cup. Simulations of plug-assist thermoforming using a temperature dependent COF showed qualitative agreement with the GSA data thereby supporting our inferences.

Mechanically tunable curcumin incorporated polyurethane hydrogels as potential biomaterials - Divakaran, Anumon V.; Azad, Lal Busher; Surwase, Sachin S.; Torris, Arun A. T.; Badiger, Manohar V. (Chemistry of Materials, 2016)
We report here on the one-pot synthesis and characterization of curcumin incorporated polyethylene glycol polyurethane (PU-CUR) hydrogels using PEG-4000, 4, 4'-methylenebis (cyclohexyl isocyanate), curcumin in the presence of a cross-linker, 1,2,6 hexanetriol (HT). Besides the physical entrapment, curcumin also provides a partial cross linking in the 3-D structure of the hydrogel. The degree of swelling in hydrogels could be controlled by varying the amount of HT as well as curcumin. The structural characterization of hydrogels was performed using Fourier transform infrared spectroscopy, high-resolution mass spectrometry, UV and fluorescence spectroscopy. The wide-angle X-ray scattering studies revealed the existence of crystalline domains of PEG, and the small-angle X-ray scattering studies showed the presence of lamellar microstructures. Porous structure in the hydrogel was created by cryogenic treatment and lyophilization. Scanning electron microscopy and microcomputed tomography imaging of hydrogels showed the presence of interconnected pores. The mechanical strength of the hydrogels was measured using a universal testing machine. The observed tensile and breaking compression strengths for the equilibrium swollen gels were found to be in the range of 0.22-0.73 MPa and 1.65-4.6 MPa, respectively. Detailed in vitro biological experiments showed the biocompatibility of gels, cytostatic dosage of curcumin, selective toxicity toward cancer cell lines, and antibacterial property. These gels show promising applications as scaffolds and implants in tissue engineering.